2010
DOI: 10.1111/j.1538-7836.2010.03767.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe hemophilia with mild bleeding phenotype: molecular characterization and global coagulation profile

Abstract: To cite this article: Santagostino E, Mancuso ME, Tripodi A, Chantarangkul V, Clerici M, Garagiola I, Mannucci PM. Severe hemophilia with mild bleeding phenotype: molecular characterization and global coagulation profile. J Thromb Haemost 2010; 8: 737-43.Summary. Background: Patients with severe hemophilia may show very varied bleeding tendencies, and the reasons for this heterogeneous clinical expression are unclear. The factor VIII/ FIX genotype is the main determinant of the residual factor activity; howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
226
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(242 citation statements)
references
References 28 publications
12
226
0
4
Order By: Relevance
“…There are in vitro and ex vivo observations showing that thrombin generation is a more sensitive parameter than factor VIII. For instance, Santagostino et al (39 ) showed that patients classified as severe hemophiliacs (factor VIII Ͻ1 IU/dL) may display different hemorrhagic phenotypes; some bleed more than others in spite of having identical levels of factor VIII. These different phenotypes were, however, distinguished by the TGA: the nonbleeders generated more thrombin than the bleeders (39 ).…”
Section: Application Of Tga To Manage Patients With Hemorrhagic Coagumentioning
confidence: 99%
See 1 more Smart Citation
“…There are in vitro and ex vivo observations showing that thrombin generation is a more sensitive parameter than factor VIII. For instance, Santagostino et al (39 ) showed that patients classified as severe hemophiliacs (factor VIII Ͻ1 IU/dL) may display different hemorrhagic phenotypes; some bleed more than others in spite of having identical levels of factor VIII. These different phenotypes were, however, distinguished by the TGA: the nonbleeders generated more thrombin than the bleeders (39 ).…”
Section: Application Of Tga To Manage Patients With Hemorrhagic Coagumentioning
confidence: 99%
“…For instance, Santagostino et al (39 ) showed that patients classified as severe hemophiliacs (factor VIII Ͻ1 IU/dL) may display different hemorrhagic phenotypes; some bleed more than others in spite of having identical levels of factor VIII. These different phenotypes were, however, distinguished by the TGA: the nonbleeders generated more thrombin than the bleeders (39 ). The logical conclusion is that thrombin generation in these patients is a more sensitive parameter than factor VIII.…”
Section: Application Of Tga To Manage Patients With Hemorrhagic Coagumentioning
confidence: 99%
“…This view is supported by the association between detectable FVIII antigen and NNAs. Measurable FVIII antigen in plasma, 38 potential contamination with maternal blood during delivery, 39 and the presence of milk fat globule epidermal growth factor-FVIII (a glycoprotein with a strong homology with circulating FVIII in breast milk) might all be examples of early exposure. 40 The presence of NNAs before any specific treatment may be the expression of a natural anti-FVIII B-cell clone that exists independently of any environmental FVIII exposure.…”
Section: Discussionmentioning
confidence: 99%
“…4 Thrombin generation assays (TGAs) measure the total amount of thrombin that can be generated in a volume of platelet-rich or plateletpoor plasma (PRP or PPP). It has been shown to be able to differ between severe and mild bleeding phenotypes, both in mild and severe haemophilia, 5,6 as well as being useful in monitoring the haemostatic effect of bypassing agents in haemophilia patients with inhibitors. 7 In this study, the response to prophylaxis was evaluated with TGA, To avoid unspecific contact activation it has been suggested that corn trypsin inhibitor (CTI) should be added on blood sampling.…”
mentioning
confidence: 99%